Algorithm for determination of the damage characteristic (C-S) curve of asphalt mixtures - de Almeida, Francisco José Pereira; Silva, Suyanne Costa; Soares, Jorge Barbosa; Parente Junior, Evandro (Transportes, 2020)
This paper presents the algorithm for calculating the damage characteristic curve obtained in direct tension tests taking into account sinusoidal controlled strain loading. The Viscoelastic Continuum Damage formulation is presented in a summarized form for the algorithm, in which the pseudo strain, at the instants associated to the observed stress, is calculated using the expression of the linear viscoelasticity stress under controlled strain testing. This facilitates subsequent treatment of the data to obtain the vs. curve. The proposed algorithm is simple to understand and easy to implement computationally. The algorithm was validated with the results of fatigue test simulations in three mixtures, which have indicated its potential.